Macrophages and tumor-associated macrophages in the senescent microenvironment: From immunosuppressive TME to targeted tumor therapy - Ming Du; Lu Sun; Jinshuai Guo; Huina Lv (Elsevier, 2024)
In-depth studies of the tumor microenvironment (TME) have helped to elucidate its cancer-promoting mechanisms and inherent characteristics. Cellular senescence, which acts as a response to injury and can the release of senescence-associated secretory phenotypes (SASPs). These SASPs release various cytokines, chemokines, and growth factors, remodeling the TME. This continual development of a senescent environment could be associated with chronic inflammation and immunosuppressive TME. Additionally, SASPs could influence the phenotype and function of macrophages, leading to the recruitment of tumor-associated macrophages (TAMs). This contributes to tumor proliferation and metastasis in the senescent microenvironment, working in tandem with immune regulation, angiogenesis, and therapeutic resistance. This comprehensive review covers the evolving nature of the senescent microenvironment, macrophages, and TAMs in tumor development. We also explored the links between chronic inflammation, immunosuppressive TME, cellular senescence, and macrophages. Moreover, we compiled various tumor-specific treatment strategies centered on cellular senescence and the current challenges in cellular senescence research. This study aimed to clarify the mechanism of macrophages and the senescent microenvironment in tumor progression and advance the development of targeted tumor therapies.